2010
DOI: 10.1136/bjo.2008.155820
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of human conjunctiva on in vivo confocal microscopy

Abstract: The age-related changes of conjunctivas included decreasing densities of DCs as well as the degeneration of subepithelial structures. Even though no significant changes in GCs densities could be seen in the different age groups, the increasing rates of conjunctival microcysts indicated that the cellular function of GCs declined while ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 19 publications
4
43
1
Order By: Relevance
“…25 Goblet cell density assessment using LSCM has been used to assess ocular surface changes related to age, 26,27 Sjögren's syndrome DE, 2,19 pterygium, 28 chemical burns, 29 glaucoma treatment with preserved and unpreserved levobunolol, 30 and tafluprost therapy. 31 To date, only one cross-sectional report of GCD assessed by LSCM in CLW has been published, which showed no significant difference between CL wearers and non-CL wearers; however, that study was limited by small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…25 Goblet cell density assessment using LSCM has been used to assess ocular surface changes related to age, 26,27 Sjögren's syndrome DE, 2,19 pterygium, 28 chemical burns, 29 glaucoma treatment with preserved and unpreserved levobunolol, 30 and tafluprost therapy. 31 To date, only one cross-sectional report of GCD assessed by LSCM in CLW has been published, which showed no significant difference between CL wearers and non-CL wearers; however, that study was limited by small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…According to Abdel-Khalek et al [12], based on the study of normal elderly population, the conjunctival epithelium shows irregularities in thickness and reduction of the number of goblet cells in the older age group (over the age of 80 years) [12]. On the other hand, some other reports concluded that the number of goblet cells did not vary significantly with age [13,14].…”
Section: Discussionmentioning
confidence: 97%
“…We used IVCM because this technique is minimally invasive, and it is effective in evaluating the histopathology of surface disease (Mastropasqua et al 2006;Messmer et al 2006;Hong et al 2010;Le et al 2010;Wakamatsu et al 2010;Zhu et al 2010) and the toxic effects of glaucoma therapy (Arici et al 2000;Messmer et al 2006;Ciancaglini et al 2008;Martone et al 2009;Bergonzi et al 2010). Our study showed that no changes occurred throughout followup in both controls and patients treated with preservative-free timolol; on the opposite, BAK-preserved eye drops were associated with signs of ocular surface inflammation (lower goblet cell density and epithelial irregularity) after 12 months of treatment.…”
Section: Discussionmentioning
confidence: 99%